2008
DOI: 10.2187/bss.22.46
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Ion Microbeam Irradiation Induces Bystander Killing of Human Cells

Abstract: Significant evidence indicates that ionizing radiation causes biological effects in nonirradiated bystander cells having received signals from directly irradiated cells. There is little information available hitherto as to the bystander effect of energetic heavy ions; however, our previous work has shown that in confluent cultures of normal human fibroblast AG01522 cells, targeted exposure of 0.0003% of cells to microbeams of 18.3 MeV/u 12 C (103 keV/µm) and 13.0 MeV/u 20 Ne (375 keV/µm) ions can similarly cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Concerning the direct intercellular interactionmediated bystander effect, the survival of human cervical cancer HeLa cells was decreased in bystanders irrespective of ion species (103-375 keV/µm) and Bcl-2 overexpression, but was less pronounced than in fibroblasts (Hamada et al, 2008g). In human lung cancer A549 cells, bystander-induced reductions in the survival were observed in a GJIC-dependent fashion (Harada et al, 2009).…”
Section: Bystander Response Of Tumor Cellsmentioning
confidence: 99%
“…Concerning the direct intercellular interactionmediated bystander effect, the survival of human cervical cancer HeLa cells was decreased in bystanders irrespective of ion species (103-375 keV/µm) and Bcl-2 overexpression, but was less pronounced than in fibroblasts (Hamada et al, 2008g). In human lung cancer A549 cells, bystander-induced reductions in the survival were observed in a GJIC-dependent fashion (Harada et al, 2009).…”
Section: Bystander Response Of Tumor Cellsmentioning
confidence: 99%
“…Bystander studies using normal human fibroblasts were performed with the focus of attention on various endpoints, such as cell survival rate, frequency of micronucleus formation, phosphorylation of histone H2AX, apoptosis, and induction of p53 protein [34][35][36][37][38][39]. Moreover, gene expression analysis of bystander cells using the DNA microarray assay revealed that the G protein/PI-3 kinase pathways were activated in the bystander cells but not in directly irradiated cells [40].…”
Section: Programmed Matrix Irradiation Without Targeting Specific Cellsmentioning
confidence: 99%
“…In the LSq fitting, we approximated that numerical values of the parameters were the same for Bcl-2 cells and Neo cells, because the nontargeted effect occurs independent of Bcl-2 overexpression [16]. We also assumed that the parameters related to the dose dependence of the triggering probability, a 1 and a 2 , were the same for all cell lines and radiation types, and their numerical values were determined from the X-ray microbeam irradiation experiment.…”
Section: Theory and Calculationmentioning
confidence: 99%
“…In this study, we determined the nontargeted model parameters except for z n,thre by the LSq fitting of the SF of Bcl-2 cells and Neo cells irradiated with heavy-ion microbeam [16] as well as that of the WI-38 normal human fibroblasts irradiated with synchrotron X-ray microbeam [30] . In these experiments, the number of Bcl-2 cells, Neo cells and WI-38 cells in each whole population, N W , was 2.67e6, 2.68e6 and 7.0e5, respectively, and such cell population sizes were determined by the conventional automatic counting of trypsinized cells.…”
Section: Theory and Calculationmentioning
confidence: 99%
See 1 more Smart Citation